Pendampingan Pendirian Koperasi Unit Desa Berbasis Syariah Di Desa Karangmukti Bungursari Purwakarta - Jalaludin, Jalaludin; Rohmat, Siti; Ina Lestari, Nurmala (STIE Syariah Indonesia Purwakarta, 2021)
This community service aims as a means of providing insight into sharia cooperatives for the community in Karangmukti Village, Kec. Bungursari Purwakarta. At the same time providing assistance and economic empowerment through the re-establishment of KUD, but based on sharia. The Village Unit Cooperative (KUD) is a microfinance institution (LKM) capable of serving the needs of the community of micro and small business actors. This institution facilitates the development of conditions (systems, methods, techniques and outputs) for the realization of a balance of wealth that does not only belong to a group of people. Simultaneously, the Sharia-Based KUD is also a forum for community synergy and creating local wisdom. Local wisdom in question is how to prepare development infrastructure based on local community participation, which does not have a permanent dependence on assistance, either from the government or others. The implementation of Sharia-Based KUD is carried out by relying on sharia rules and existing cooperative rules as long as they do not conflict with sharia law. The strength of the spiritual and social values ​​of the Sharia-based KUD is the advantage of sharia-based cooperatives over conventional village unit cooperatives. In carrying out this service program, it will be carried out by using a method approach; preparation, learning, and re-establishment of Sharia-Based KUD